Case report: Successful treatment of intestinal leiomyositis in a dog using adjunctive intravenous immunoglobulin - Olivarez, Michelle Patrick; Williams, Jarod; Udomteerasuwat, Nutnapong; Corner, Sarah; Byers, Christopher (Frontiers in Veterinary Science, 2024)
A 10 year old female spayed Dachshund canine presented with abdominal pain and generalized severe ileus. Exploratory laparotomy performed confirming severe ileus of undetermined origin. Multiple intestinal biopsy results confirmed acute intestinal leiomyositis. IHC stains confirmed T-cell predominant inflammatory infiltrate.Intravenous immunoglobulin hIVIG was administered prior to immunosuppressive therapy. Return of functional peristaltic activity and resolution of symptoms was observed within 10-days of hIVIG treatment. Long term management with functional peristaltic recovery was achieved with combined therapy including mycophenolate.hIVIG treatment requires additional study to investigate potential benefit in the stabilization phase of this commonly fatal, treatment-refractory disease.